CHALLENGES OF STUDENT LEARNING PROBLEMS IN THE DIGITAL ERA: A SCHOOL COUNSELOR'S PERSPECTIVE - Saputra, Nur Mega Aris; Muslihati, Muslihati; Ramli, M; Sobri, Ahmad Yusuf; Jalil, M. Khoirudin; Rafli, Muhammad (Program Studi Bimbingan dan Konseling Universitas Tunas Pembangunan Surakarta, 2025)
Students’ learning problems in schools are issues that require serious attention from all stakeholders, particularly school counselors. Various factors contribute to the learning difficulties experienced by students today. Changes in curriculum, educational systems, and technological developments have significantly influenced the nature of students’ learning problems. In addition, challenges in other domains such as personal, social, and even career-related aspects also affect students’ academic functioning. These learning problems consistently appear every year, making them recurring challenges that school counselors must address in their service delivery, both now and in the future. Drawing from the experiences of school counselors in managing and providing services related to students’ learning difficulties, this study focuses on exploring the challenges of learning problems faced by junior high school students from the counselors’ perspectives. A qualitative research method with a phenomenological design was employed, involving school counselors with more than five years of professional experience. The data obtained were then analyzed in depth to answer the central research question regarding the challenges of student learning problems in the digital era. The findings indicate that in the current digital era, the primary underlying factor contributing to students’ learning problems is low learning motivation. This condition is influenced by excessive use of social media and online games. Another contributing factor is students’ perception that learning is unimportant, along with the belief that studying is a boring activity. These issues highlight the need for serious attention from all relevant parties, as low learning motivation among students must be addressed as a priority.